A teoria dialógica de Bakhtin na análise da publicidade: sustentabilidade e ato ético - Knoll, Graziela Frainer (2013)
Bakhtin's ethical act establishing thought that humans are entirely responsible for their actions. Understood this way, there s a concrete act of a subject that is historically situated, immersed in social relations and dialogically constituted. The corporate discourse of sustainability is part of the ethical discourses currently circulating in the social environment, with visibility in various spheres of activity, including advertising. So the following questions arise: What ethical and cultural values are conveyed in sustainability advertising? How such values are arranged in hierarchies in the ads? The aim of this work is to analyze, through the dialogical theory, the central hypothesis that there are recurrences, to some extent, on the values and the hierarchy of values in samples of the discourse of sustainability in print advertising. As specific objectives, are proposed: a) to investigate how ethical and cultural values are constructed and expressed through language in the materials; b) to describe verb-visual occurrences that are present in the advertisements c) to understand the relationship between the analyzed texts and the social context. As theoretical and methodological support, we used the dialogic theory of Bakhtin Circle (BAKHTIN, 2010a, 2010b; VOLOCHÍNOV, 2009, 2011) articulated with the Thompson s media theory (2007) and rhetorical categories on values by Perelman and Olbrechts- Tyteca (2005). Five Banks advertisements were analyzed, three from Santander and two from Banco do Brasil, that were published at Veja magazine and selected in the period between January 2010 and January 2012. The methodology follows Bakhtin and it was developed based on dialogism of language. The dialogic theory contemplates the relationship between text and context. These data were considered: a) contextual data from the corporate websites of these banks and social, discoursive and cultural framework that surrounds the advertising sphere; b) textual data, mainly from the Bakhtinian notions of ideological sign and evaluative intonation (VOLOCHÍNOV, 2009; BAKHTIN, 2010a) and concepts of values, hierarchy of values and commonplaces of argumentation (PERELMAN; OLBRECHTS-TYTECA, 2005). The results show that there are recurrences, as well as peculiarities in the way the ads from Santander and Banco do Brasil produce and convey values in the social context. As an ethical value, sustainability is present in the analyzed advertisements, being sustained and reproduced by the discourse of corporate social responsibility that is also present in the websites of these banks. Sustainability is presented by both institutions as an ethical value to be pursued by the Bank and its customers. However, some differences are observed in how values are arranged in a hierarchy by each institution: for Santander, sustainable development is connected to the financial value, for the Banco do Brasil, sustainability is restricted to water preservation. The advertising language in the analyzed utterances builds ideological-discoursive positions that value sustainability within a corporate and capitalist context in which assuming social responsibility is advantageous for the company. Allied to the understanding that just as there are language practices that precede us, there are practices that are part of our contemporary experience in the world, the analyzed texts materialize dialogic relationships that integrate these discourses.